2010
DOI: 10.1111/j.1420-9101.2010.02092.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutualism variation in the nodulation response to nitrate

Abstract: The evolution of mutualisms under novel selective pressures will play a key role in ecosystem responses to environmental change. Because fixed nitrogen is traded in plant–rhizobium mutualisms, increasing N availability in the soil is predicted to alter coevolution of these interactions. Legumes typically decrease the number of associations (nodules) with rhizobia in response to nitrate, but the evolutionary dynamics of this response remain unknown. We grew plant and rhizobium genotype combinations in three N e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 45 publications
6
107
1
Order By: Relevance
“…In particular, plant biomass with the same combination of AMF and rhizobia varied between phosphorus addition treatments. This result is consistent with other studies that find plant response to the effects of nutrient addition on plant-AMF (Vogelsang et al 2006) and plant-rhizobia interactions (Heath et al 2010) is dependent upon host-symbiont combination. Yet we found that nitrogen did not influence the effect of the AMF-rhizobia combination.…”
Section: Abiotic Context Dependency Of Plant-amf-rhizobia Interactionssupporting
confidence: 93%
See 1 more Smart Citation
“…In particular, plant biomass with the same combination of AMF and rhizobia varied between phosphorus addition treatments. This result is consistent with other studies that find plant response to the effects of nutrient addition on plant-AMF (Vogelsang et al 2006) and plant-rhizobia interactions (Heath et al 2010) is dependent upon host-symbiont combination. Yet we found that nitrogen did not influence the effect of the AMF-rhizobia combination.…”
Section: Abiotic Context Dependency Of Plant-amf-rhizobia Interactionssupporting
confidence: 93%
“…This result conflicts with another study which showed that nodulation of Medicago sativa decreased with AMF infection (Vazquez et al 2001). A recent study by Heath et al (2010) demonstrated that the effects of nitrogen levels on nodulation were variable between M. truncatula and rhizobia genotypes. Our results indicate that AMF colonization can also mediate the effect of nutrient level on nodulation.…”
Section: Competitive or Beneficial Effects Between Amf And Rhizobiacontrasting
confidence: 63%
“…Since coevolutionary responses on post-infection traits are currently intensely debated [20,22,24,25,59], more data on genetic variation in symbiosisrelated traits (e.g. nodule size [65], energy storage in rhizobia [66]) and post-infection stabilizing traits, as well as the strength of natural selection acting on them, would clarify their role in stabilizing or destabilizing mutualisms [19]. Similarly, identifying trait mismatches between species due to differing coevolutionary histories (cf.…”
Section: Discussionmentioning
confidence: 99%
“…In legumes, it has been determined that nitrate is involved in the regulation of nodulation (Heath et al 2010;Saito et al 2014). Nitrate transporters are thus likely to have important roles to play during symbiosis establishment.…”
Section: Nitrate Transporters and Their Possible Roles In Rhizobial Smentioning
confidence: 99%